2015
DOI: 10.1007/s00011-015-0886-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of vicenin-2 and scolymoside in vitro and in vivo

Abstract: Vicenin-2 and scolymoside possess anti-inflammatory functions by inhibiting hyperpermeability,expression of CAMs, and adhesion and migration of leukocytes, thereby endorsing its usefulness as a therapy for vascular inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…The semi-flexible docking results of CDOCKER revealed that pachymic acid and vicenin-2, as examples, formed interactions with HO-1 and ERK, respectively (Supplementary Figure 1). These results for compound-protein interactions between pachymic acid-HO-1 and vicenin-2-ERK were confirmed and validated against published articles (Lu et al, 2010;Kang et al, 2015). In summary, natural small molecules for specific pharmacodynamic targets against cardiovascular diseases could be screened out conveniently, quickly, and successfully by using the CPSD strategy.…”
Section: Cpsd In the Development Of Cardiovascular Disease Drugssupporting
confidence: 67%
“…The semi-flexible docking results of CDOCKER revealed that pachymic acid and vicenin-2, as examples, formed interactions with HO-1 and ERK, respectively (Supplementary Figure 1). These results for compound-protein interactions between pachymic acid-HO-1 and vicenin-2-ERK were confirmed and validated against published articles (Lu et al, 2010;Kang et al, 2015). In summary, natural small molecules for specific pharmacodynamic targets against cardiovascular diseases could be screened out conveniently, quickly, and successfully by using the CPSD strategy.…”
Section: Cpsd In the Development Of Cardiovascular Disease Drugssupporting
confidence: 67%
“…However, the activity observed in this present study did not conform to those results. The flavones scolymoside, present only in the C. subternata extracts, but in substantial quantities, and vicenin-2, with the highest concentration in C. genistoides extracts, elicited anti-inflammatory activity in various systems [36,37]. Nevertheless, their concentration in the extracts also did not correlate with their immune-regulating activity, suggesting that some other compounds or synergistic effects of several molecules would contribute to the activity observed in our experiments.…”
Section: Discussionmentioning
confidence: 58%
“…The naringin dihydrochalcone biological effects were not analysed to present days, however its major constituent the naringin was suggested to be the main component of Ganshuang granule that plays an anti-fibrotic role through deactivation of hepatic stellate cells in cirrhotic mouse model [42], and through the attenuation of EGFR/ERK signalling could suppress cancer cell growth [43]. In the case of vicenin-2 has been recently shown that can suppress high-glucose induced vascular inflammatory processes in human umbilical vein endothelial cells and mice, thereby suggesting its effectiveness as a therapeutic agent for vascular inflammatory diseases [44,45].…”
Section: Resultsmentioning
confidence: 99%